Islamic Environmental Ethics and the Grammar of Permanence: Reading Ontology, Contingency, and Covenant in Sūrat Al-Fātiḥah - Zein Muchamad Masykur (Prodi Ilmu Lingkungan Fakultas Sains dan Teknologi, 2026)
While Islamic environmental ethics has matured significantly, it remains anchored in thematic and doctrinal readings of the Qurʼān, largely overlooking the ecological commitments embedded within the text’s grammatical architecture. This article addresses this gap by utilizing Arabic linguistic theology to provide a philosophical reinterpretation of Sūrat Al-Fātiḥah. By analyzing the surah’s structural reliance on nominal forms (jumlah ismiyyah) over finite verbs (fiʼl), this study uncovers a sophisticated framework for valuing the natural world. Using conceptual analysis and ecotheological synthesis, the article advances three core claims: first, the surah’s nominal dominance suggests an ontology of permanence that challenges anthropocentric instrumentalism; second, its use of finite verbs constructs an “eco-ethical anthropology of radical contingency,” positioning humanity as dependent stewards rather than sovereign agents; and third, its dialogic structure establishes a covenantal framework that binds human accountability to the Rabb al-ʼālamīn (Lord of all worlds). By placing these linguistic features in dialogue with contemporary climate science and environmental ethics, this study demonstrates that a hermeneutically disciplined reading can reveal—rather than impose—the profound ecological resonance inherent in the Qur’anic text.